Short Lifespans of Memory T-cells in Bone Marrow, Blood, and Lymph Nodes Suggest That T-cell Memory Is Maintained by Continuous Self-Renewal of Recirculating Cells - Baliu-Piqué, Mariona; Verheij, Myrddin W.; Drylewicz, Julia; Ravesloot, Lars; de Boer, Rob J.; Koets, Ad; Tesselaar, Kiki; Borghans, José A. M. (Frontiers in Immunology, 2018)
Memory T-cells are essential to maintain long-term immunological memory. It is widely accepted that the bone marrow (BM) plays a crucial role in the long-term maintenance of memory T-cells. There is controversy however on the longevity and recirculating kinetics of BM memory T-cells. While some have proposed that the BM is a reservoir for long-lived, non-circulating memory T-cells, it has also been suggested to be the preferential site for memory T-cell self-renewal. In this study, we used in vivo deuterium labelling in goats to simultaneously quantify the average turnover rates – and thereby expected lifespans – of memory T-cells from BM, blood and lymph nodes (LN). While Ki-67 expression, a snapshot marker for recent cell division, was higher in memory T-cells from blood compared to BM and LN, in vivo deuterium labelling revealed no substantial differences in the expected lifespans of memory T-cells between these compartments. Our results support the view that the majority of memory T-cells in the BM are self-renewing as fast as those in the periphery, and are continuously recirculating between the blood, BM and LN.